Technologies for Business Information Systems - Abramowicz, Witold; Mayr, Heinrich C. (Springer Netherlands : Imprint: Springer, 2007)
Technologies for Business Information Systems The material collected in this book covers a broad range of applications of c- puter science methods and algorithms in business practice. It presents a research cutting edge in development, implementation, and improvement of computer s- tems. We publish this book with intention that it helps to establish strong foun- tions for further development of research in this area and support people involved in business computer applications, those implementing computer technology in industry. The computer science and information systems topics covered in the book include data warehouses, ERP, XML, ontologies, rule languages, Web s- vices. We divided the chapters into several areas of applications of the above. There are parts on modeling business processes, devoted to applications of formal methods and metrics that assist this crucial step for contemporary heavy-IT o- ented enterprises. This is accompanied by chapters on information systems c- sidered both from engineering and social perspectives. Particular topics on so- ware engineering have been placed in a separate book part. We addressed also advancements in information retrieval and formal representation of knowledge - ing ontologies and rule languages. These topics are worth of interest due to their reemergence in recent years, significant advances and broad range of potential as well as actual applications. Last but not least comes the other area of applying IT - e-government. Several authors elaborate on methods and experiences of IT adoption for administrative purposes.